Thymoquinone inhibits proliferation in gastric cancer via the STAT3 pathway in vivo and in vitro - Zhu, Wen-Qian; Wang, Jun; Guo, Xu-Feng; Liu, Zhou; Dong, Wei-Guo (World journal of gastroenterology : WJG, 2016)
AIM: To elucidate the mechanism of thymoquinone(TQ)-induced apoptosis in human gastric cancer cells in vitro and in vivo.METHODS: HGC27, BGC823, and SGC7901 cells were cultured in vitro and treated with TQ(0, 10, 25, 50, 75, 100, 125 μmol/L) for 12 h, 24 h, and 36 h, and then the proliferation inhibitory rates were detected by methylthiazole tetrazolium assay. Apoptosis was observed after Hoechst staining. The protein expressions of signal transducer and activator of transcription(STAT)3, p-STAT3, STAT5, p-STAT5, phospho-janus-activated kinase 2(JAK2), JAK2, p-Src, Src, glyceraldehyde-3-phosphate dehydrogenase, lamin-A, survivin, Cyclin D, Bcl-2, Bax, peroxisome proliferator activated receptor, and caspase-3,7,9 were detected by western blot. Cell cycle and apoptosis weredetermined with flow cytometry. TQ induced dosedependent apoptotic cell death in HGC27 cells was measured by Annexin V-fluorescein isothiocyanate(FITC)/propidium iodide(PI) analysis and Hoechst 33258. RESULTS: TQ inhibited the phosphorylation of STAT3 but not STAT5. TQ-induced downregulation of STAT3 activation was associated with a reduction in JAK2 and c-Src activity. TQ also downregulated the expression of STAT3-regulated genes, such as Bcl-2, cyclin D, survivin, and vascular endothelial growth factor, and activated caspase-3,7,9. Consistent with the in vitro results, TQ was significantly effective as an antitumor agent in a xenograft tumor mouse model. CONCLUSION: This study provides strong evidence that downregulation of the STAT3 signaling pathway mediates TQ-induced apoptosis in gastric cancer.